2022
DOI: 10.1128/mbio.01447-22
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Minimal Selective Concentrations and Fitness Costs during Biofilm and Planktonic Growth

Abstract: Our understanding of how and where antibiotic resistance is selected in response to antibiotic exposure is still limited, and this is particularly true for selective processes when bacteria are growing in biofilms, arguably the most significant mode of growth of bacteria in human and animal infections as well as in other settings. In this study, we compared how different types of resistant E. coli strains were selected in response to antibiotic exposure during planktonic and biofilm gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…Evolved biofilm populations maintain a higher diversity than corresponding planktonic populations, in which successful mutations reach fixation quickly, and the biofilm environment may protect against negative selection of less fit resistant mutants that would be quickly outcompeted in planktonic cultures 121 . However, a recent study indicated that fitness costs for resistance in surfaceassociated E. coli biofilms did not differ from those in planktonic cultures 79 . In addition, another recent study has shown that the specific environment co-determines fitness and resistance levels associated with specific mutations 131 .…”
Section: Looking At Biofilm Antimicrobial Susceptibility Through the ...mentioning
confidence: 93%
See 4 more Smart Citations
“…Evolved biofilm populations maintain a higher diversity than corresponding planktonic populations, in which successful mutations reach fixation quickly, and the biofilm environment may protect against negative selection of less fit resistant mutants that would be quickly outcompeted in planktonic cultures 121 . However, a recent study indicated that fitness costs for resistance in surfaceassociated E. coli biofilms did not differ from those in planktonic cultures 79 . In addition, another recent study has shown that the specific environment co-determines fitness and resistance levels associated with specific mutations 131 .…”
Section: Looking At Biofilm Antimicrobial Susceptibility Through the ...mentioning
confidence: 93%
“…There is no information on which concentration range constitutes the mutant selection window (MSW, Box 1 ) for biofilms and various aspects of biofilm biology likely affect this window 90 , 91 . While it has been predicted that biofilm growth leads to shifts and distortions of the MSW 91 , recent work with E. coli showed that minimal selective concentration values (for five different antibiotics) did not differ between planktonic cultures and biofilms 79 . Due to the uncertainty concerning the biofilm MSW, antibiotic concentrations are often selected based on the MIC 70 or on the minimal biofilm inhibitory concentration 74 .…”
Section: Tools To Study Experimental Evolution In Biofilmsmentioning
confidence: 97%
See 3 more Smart Citations